ПЕРСПЕКТИВИ ВИКОРИСТАННЯ ЕЛЕКТРИЧНИХ АПАРАТІВ В РАМКАХ КОНЦЕПЦІЇ SMART GRID - Лупіков , В.С.; Болюх , В.Ф.; Байда , Є.І.; Крюкова , Н.В.; Варшамова , І.С.; Лелюк , М.А.; Литвиненкоo, В.В. (Інститут електродинаміки НАН України, Київ, 2012)
Analysis of the Smart Grid concept are resulted regarding of electric devices using . Primary tasks of electric devices development and their decision are formulated. References 4.